Remarks about the accommodation of the ILO 169 Convention criteria about self-identification in the Peruvian legal system - Duque Morales, Darwin (2018)
Census 2017 had a controversial question regarding indigenous identity. Media tried to explain it, and intended to help citizens to find their answer. But no one lay out the reason for such a question. The reason is related with the indigenous consciousness criteria stablished at the ILO Convention 169, and with the fact that, when the Convention was adapted to Peruvian legal system those criteria were changed. This paper will try to explain that failure implementing the treaty and will suggest a possible solution because the indigenous identity has a major impact on the global indigenous rights, especially regarding their right to prior consultation.